Wspomnienia Nikołaja Złotowratskiego próbą zażegnania kryzysu pisarza narodnika - Grącka, Monika (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The Narodnik ideology was formed at the end of 1860s. Nikolai Zlatovratski represented its liberal section which was focused on the propagation in the Russian literature the local country community (Russian – obszczina) and the fight to improve peasants’ fate in the Russian reality after granting them property rights. Like many other Narodnik activists of the 1880s (after the assassination attempt on the tsar Aleksandr ll) the writer went through the ideological identity crisis. The article analyses the work of the N. Zlatowratski including his memories written at the end of his creative path they presented the author’s searching for the source of his beliefs and an attempt to define their rightness again.